2014
DOI: 10.6116/kjh.2014.29.6.7.
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination effect of anti-obesity in the extracts of Phyllostachys pubescence Mael and Scutellaria baicalensis Georgi

Abstract: Objectives : Anti-obesity drugs that have been developed so far have limited efficacies and considerable adverse effects affecting tolerability and safety. Therefore, most anti-obesity durgs have been withdrawn. We tried to develop anti-obesity agent by combinations from herbs that are used in food ingredients as well as in traditional medicines. Methods : The 80% (v/v) ethanol extracts from Bamboo (Phyllostachys pubescence) leaf (BL) and Scutellaria baicalensis (SB) and their 1:1 combination (BLSB) was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Phyllostachys pubescens leaf (bamboo leaf: BL) and Scutellaria baicalensis root (SB) showed the most reliable antiobesity effects among the plants that we investigated. We found that the 1 : 1 (w/w) mixture of the two plants extracts demonstrated synergistic antiobesity effects [ 20 ]. In this study, after exploring the antiobesity effects of the two plants, we investigated whether the different combinations of the two plants extracts' mixtures have effects on antiobesity or not.…”
Section: Introductionmentioning
confidence: 99%
“…Phyllostachys pubescens leaf (bamboo leaf: BL) and Scutellaria baicalensis root (SB) showed the most reliable antiobesity effects among the plants that we investigated. We found that the 1 : 1 (w/w) mixture of the two plants extracts demonstrated synergistic antiobesity effects [ 20 ]. In this study, after exploring the antiobesity effects of the two plants, we investigated whether the different combinations of the two plants extracts' mixtures have effects on antiobesity or not.…”
Section: Introductionmentioning
confidence: 99%
“…Body weight, total fat weight, liver weight, TG, HDL, AST, hepatic lipid accumulation, gene expression 2 11) Body weight, gene expression 3 12) Body weight, food intake, (periepididymal, perirenal) adipose tissue weight, adiponectin, leptin, insulin, TC, TG, HDL 4 13) Body weight, food intake, fooe efficiency, liver weight, abdominal fat weight, white adipose tissue weight, TC, TG, HDL, LDL, GOT, GPT, leptin, adiponectin, hepatic content (total lipid, TG), gene expression 5 14) Body weight, liver weight, adipose tissue weight, AST, ALT, TC, TG, AI, HDL, LDL, adiponectin, cell number of adipose tissue 6 15) Body weight, food intake, liver weight, glucose, insulin, TC, HDL, GOT, GPT, size of epididymal adipocyte 7 16) Glucose, OGTT, ATM, gene expression 8 17) Body weight, food intake, food efficiency, adipose tissue weights, adipose tissue size, gene expression 9 18) Body weight, weights of liver and adipose tissue 10 19) Body weight, adipose tissue weights, FER, leptin, TG, glucose, insulin, hepatic lipid accumulation, number and size of (inguinal, epididymal) adipocytes 11 20) Body weight, HDL, LDL 12 21) Body weight, liver and abdominal fat weight, total cholesterol, TG, HDL, LDL, glucose, GOT, GPT 13 22) Body weight, glucose, total cholesterol, LDL 14 23) Body weight, food efficiency, white adipose tissue and liver weight, TG, total cholesterol, LDL, leptin, adiponectin, fat volume, hepatic lipid accumulation, hepatic content (total lipid, TG, total cholesterol), gene expression 15 24) Body weight, food intake, epididymal adipose tissue weight, AST, ALT, TG, total cholesterol, LDL, HDL, leptin, liver tissue 16 25) Free fatty acid, TG, total cholesterol, LDL, HDL, TBARS, IL-1β, IL-6, TNF-α, IL-10, NO, liver content (total cholesterol, TG, TBARS, GSH-Px, SOD, CAT), gene expression 17 26) Body weight, adipose tissue weights, FER, leptin, TG, glucose, insulin, cell number and size of (inguinal, epididymal) adipose tissue, liver fibrosis 18 27) Body weight, adipose tissue weights, FER, TG, glucose, cell number and size of (inguinal, epididymal) adipose tissue, liver fibrosis 19 28) Body weight, total cholesterol, TG, HDL, gene expression 20 29) Body weight, FER, liver weight, total cholesterol, LDL, HDL, glucose, ALT, creatinine, viceral adipose, liver tissue, epididymal adipose tissue 21 30) Total cholesterol, glucose, gene expression 22 31) Body weight, total cholesterol, gene expression 23 32) Body weight, food intake, FER, liver weight, abdomal fat weight, epididymal and peri...…”
Section: Simplementioning
confidence: 99%
“…C57bl/6j 6 M High fat diet 2 Ye et al (2016) 11) C57bl/6j 6 M High fat diet 3 Oh et al (2016) 12) C57bl/6j 7 M High fat diet 4 Lee et al (2016) 13) C57bl/6 6 M High fat diet 5 Jang et al (2016) 14) Icr 4 -High fat diet 6 Song et al (2016) 15) C57bl/6 5 M High fat diet 7 Ma et al (2015) 16) C57bl/6 -M High fat diet 8 Kim et al (2015) 17) C57bl/6 5 M High fat diet 9 Choi et al (2015) 18) Icr 5 F High fat diet 10 Yoo et al (2015) 19) C57bl/6n 7 M High fat diet 11 Kim et al (2015) 20) C57bl/6 4 -High fat diet 12 Youn et al (2015) 21) Icr 6 F High fat diet 13 Min et al (2015) 22) C57bl/6 4 -High fat diet 14 Keum et al (2015) 23) C57bl/6j 6 M High fat diet 15 Kee et al (2014) 24) SD -M High fat diet 16 Lee et al (2014) 25) SD -M High fat diet 17 Seok et al (2014) 26) C57bl/6n 7 M High fat diet 18 Kim et al (2014) 27) C57bl/6n 7 M High fat diet 19 Shin et al (2014) 28) SD -F Estrogen deficient 20 Kang et al (2014) 29) C57bl/6 10 M High fat diet 30) Icr 6 M High fat diet 22 Lee et al (2014) 31) C57bl/6j 8 M High fat diet 23 Yoon et al (2014) …”
mentioning
confidence: 99%